Attitudes analyses of mobility disorders adolescents’ parents in regards of improvement social and household skills - Ghazaryan, Tatevik
The purpose of this study is to analyse the attitudes of parents of adolescents with mobility disorders regarding the need to improve their children's social and household skills. The methodology of data collection, processing and analysis of the research is based on the approach of quantitative methods, which allows combining the collection of quantitative data, using quantitative methods, later having the opportunity to conclude the data obtained through certain numerical patterns. The specially designed questionnaire was administered to 125 parents of adolescents with mobility disorders. The survey showed that the vast majority of parents consider their children's independent life as a priority. The need to teach their children social and household skills such as shopping, cooking, cleaning kitchen utensils and the area, helping with household chores is also mentioned as quite important. At the same time, the insufficient awareness of parents about the idea of living an independent life, the inconsistency of adolescents' ability to carry out household activities, the inconsistency between their subjective perceptions, as well as the overprotection possibility of one of the traditional Armenian cultural features should be mentioned too.
Keywords: Psychology; Mobility disorders